Subject tolerance of 7 T MRI examinations - Versluis, Maarten J.; Teeuwisse, Wouter M.; Kan, Hermien E.; van Buchem, Mark A.; Webb, Andrew G.; van Osch, Matthias J. (Journal of magnetic resonance imaging, 2013)
Purpose: To determine the subjective experiences and the sources of discomfort for subjects undergoing 7 T magnetic resonance imaging (MRI) examinations on a whole‐body 7 T system in a hospital setting Materials and Methods: A postscan survey was filled out by 101 healthy subjects who participated in a 7 T examination. All participants answered questions regarding different potential sensations of discomfort including dizziness, claustrophobia, and scanner noise. Results: Dizziness was reported most frequently, with 34% of subjects experiencing dizziness while moving into the scanner and 30% while moving out of the magnet. Scanner noise was also frequently mentioned as uncomfortable (33% of the subjects). In 11% of the cases a metallic taste was reported. The overall experience was rated by 3% as unpleasant, 51% as neutral, and 46% as pleasant. Conclusion: The reported side effects are larger than previously reported for lower field strengths. However, overall, 7 T examinations are well tolerated, with only 3% of subjects rating it as unpleasant. These results agree well with previous in‐depth studies, and provide further evidence that 7 T MRI would be accepted by patients in clinical practice. J. Magn. Reson. Imaging 2013;38:722–725. © 2012 Wiley Periodicals, Inc.